Frequency and allele burden of CALR mutations in Chinese with essential thrombocythemia and primary myelofibrosis without JAK2V617F or MPL mutations. Issue 5 (May 2015) - Li, Ning; Yao, Qiu-Mei; Gale, Robert Peter; Li, Jin-Lan; Li, Ling-Di; Zhao, Xiao-Su; Jiang, Hao; Jiang, Qian; Jiang, Bin; Shi, Hong-Xia; Chen, Shan-Shan; Liu, Kai-Yan; et al.
Abstract CALR mutations are detected in about 50% of persons of predominately European descent with essential thrombocythemia (ET) or primary myelofibrosis (PMF) with wild-type alleles of JAK2 and MPL. We studied 1088 Chinese with diverse myeloproliferative neoplasms including ET (N = 234) and PMF (N = 50) without JAK2V617F or MPL exon 10 mutations. CALR mutation was detected in 53% (95% CI, 46–60%) of subjects with ET and 56% (95% CI, 41–70%) of subjects with PMF. 152 CALR mutations were identified clustering into 15 types including deletions (N = 8), insertions (N = 3) and complex indels (N = 4). We also identified 9 new mutations. Mean (±SD) mutant allele burden was 31 ± 12% (range, 0.5–69%). Persons with PMF had higher CALR mutant allele burdens than those with ET (38 ± 8% vs. 29 ± 12%; P < 0.001). Amongst persons with CALR mutations, those with PMF had different clinical features from those with ET. These data may be useful for diagnosing ET and PMF in Chinese who are about 40% of all persons with ET and PMF and for monitoring therapy-response. They also highlight similarities and differences in CALR mutations between Chinese and persons of predominately European descent with these diseases.